Guinea pig (Cavia porcellus) drinking preferences: do nipple drinkers compensate for behaviourally deficient diets?. Issue 5 (23rd July 2016) - Balsiger, A.; Clauss, M.; Liesegang, A.; Dobenecker, B.; Hatt, J.‐M.
Summary: When offered diets with hay ad libitum, rabbits ( Oryctolagus cuniculus ) clearly prefer open dishes over nipple drinkers, but whether this preference also applies in guinea pigs ( Cavia porcellus ) is unsure. We tested the drinker preference of 10 guinea pigs when offered open dishes (OD) and nipple drinkers (ND) simultaneously and measured the amount of water consumed by each animal on four different diets (grass hay 100%, or as 10% of intake on diets of fresh parsley, seed mix or pelleted complete feed, respectively) on either of the drinking systems. All animals ingested the hay portion of the combined diets first. The amount of water consumed differed significantly between individual animals. Animals drank less water on parsley than on the other diets. Nine of 10 animals clearly preferred ND when having a choice, and eight of these drank more when on ND only. The difference between the drinking systems was not consistent across all diets: on hay, similar amounts of water were drunk when on OD or ND only. Differences in water intake were reflected in urine production. Because drinking from ND in guinea pigs involves jaw movements similar to those in chewing, the results could suggest that when motivation for oral processing behaviour is not satisfied by a diet, animals may respond in using ND beyond physiological water necessity. Whereas physiological water requirements are probably better investigated with other drinking systems due to a possible overestimation when using ND, offering ND to pet guinea pigs most likely offers a form of behavioural enrichment that at the same time may increase water intake and hence act as prophylaxis against urolithiasis.